TRANSFORMASI DIRI DAN KOMUNITAS MELALUI PROGRAM PEMBINAAN WARGA GEREJA: STUDI TEOLOGIS DAN PRAKTIS - Hutabarat, Johannes; Suhendra (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
Church community development programs play a crucial role in building strong faith foundations and facilitating both personal and communal transformation. This study explores how such programs can serve as vehicles for individual spiritual growth and the strengthening of congregational identity and solidarity. Using a literature review and theological practical analysis, this research finds that church formation is not only intrapersonal but also intersocial, creating a dynamic and relevant faith ecosystem amidst modern challenges. The findings highlight the need to integrate doctrinal, relational, and service oriented dimensions in church formation to effectively respond to fragmented faith and social disengagement among congregants. This study contributes novelty by presenting a holistic formation model that combines theological, psychological, and social aspects within the context of local Indonesian churches.